GAMBARAN PENGETAHUAN DAN KONSUMSI TENTANG SAYUR DAN BUAH PADA ANAK SEKOLAH DASAR NEGERI 35 PONTIANAK UTARA - Widyana Lakshmi Puspita; Ikawati Sulistyaningsih; Khairunnisa Kurniasih (Jurusan Gizi Poltekkes Pontianak, 2025)
Vegetables and fruits are food sources rich in vitamins and minerals that are very beneficial for health, development, and growth. Consumption of vegetables and fruits is needed to grow as a source of vitamins, minerals and fiber in achieving a healthy diet according to the recommendations of balanced nutrition guidelines for optimal health. Based on data from the Indonesian Health Survey in 2023, Indonesia shows that children aged 5 years and over, including elementary school children, have a low consumption of vegetables and fruits, reaching only 11.8% of their daily needs. In West Kalimantan, the consumption of vegetables and fruits is less than 10.0% of their daily needs. This study is to determine the description of knowledge and consumption of vegetables and fruits in children of State Elementary School 35 North Pontianak. The data that will be used is primary data and secondary data that has included the amount of vegetables and fruits consumed. This study is to determine the description of knowledge and consumption of vegetables and fruits in children of State Elementary School 35 North Pontianak. The data that will be used are primary data and secondary data which includes the amount of vegetables and fruits consumed. The results of this study found 57.4% of 31 students with poor knowledge, 75.9% of 41 students with poor vegetable consumption, 63.0% of 44 students with poor fruit consumption, 81.5% of 31 students with non-diverse vegetable types and 57.4% of 31 students with non-diverse fruit types. Based on the results of this study, the level of knowledge, type, and amount of vegetable and fruit consumption is quite high which is still lacking. In this study, it is necessary to provide education and demonstrations about vegetables and fruit in children of State Elementary School 35 North Pontianak.